Development of low noise, variable high gain amplifier for signal conditioning circuit - Tan, Chee Leong; Pukhraj, Vaya, Dr. (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/